Effectiveness of heel cord stretching versus golf ball roll exercises among college students with flat foot: a pilot study - Logeshwari V; Sathya Siva; Boopathy D; Madhubala V; Prathap Suganthirababu (Фізична реабілітація та рекреаційно-оздоровчі технології, 2025)
Purpose. A common musculoskeletal disease called flat foot or pes planus is defined by the collapse or flattening of the foot's medial longitudinal arch. This disorder may result in biomechanical changes that impact posture, walking, and general lower limb function. It is common in young adults including college students who may suffer from foot pain, exhaustion, and diminished physical performance as a result of misaligned feet. The aim of the study is to compare the effect of heel cord stretching versus golf ball roll exercise among college students with flat feet.